The Role of Inspirational Teachers in Increasing Students’ Learning Motivation - Maba, Wayan; Mantra, Ida Bagus Nyoman; Widiastuti, Ida Ayu Made Sri (Pancasila International Journal of Applied Social Science, 2025)
The role of teachers in increasing students’ motivation is an essential aspect of the learning process that cannot be overlooked. The method used in this study is qualitative research design. Data was collected through interviews, classroom observations, and document studies. This study found that teachers are essential in increasing students' motivation. Teachers use various strategies, such as creating a stimulating classroom environment, using variable learning methods, providing feedback, and developing emotional bonds with students. A teacher who can instill enthusiasm and hope in students is capable of creating a fun and motivating learning environment. Moreover, this study found that active teacher involvement significantly impacts students’ satisfaction and optimal learning outcomes. This study implies that teachers should continually improve students' motivation to make learning activities more effective.